Lignocellulosic Characterizations of Indonesian Rice and The Expression Analyses of OsCAD2 and OsMYB55/61 Related To Lignin Biosynthesis - Dwi Widyajayantie; Sintho Wahyuning Ardie; Bambang Sapta Purwoko; Raden Permana Budi Laksana; Maya Ismayati; Takuji Miyamoto; Toshiaki Umezawa; Satya Nugroho (Annales Bogorienses, 2022)
Plant cell walls as sources of lignocellulosic biomass are abundant and used in diverse applications. Lignocellulosic contents manipulation can be applied to develop biomass plants. This study aimed to determine the lignocellulosic components, expressions patterns of OsCAD2 and OsMYB55/61 related to lignin biosynthesis, and deposition patterns of lignin in previously determined three low and three high total lignin content rice accessions based on TGA method. The total Klason and acid-soluble lignin showed variations between 18.03-24.53%, consistent with the TGA method. The ash content of the low lignin content (12.50-21.68%) were significantly differed from the high lignin content (24.84-27.91%) accessions. The extractive, α-cellulose, and hemicellulose contents in each accession showed almost similar proportion. Py-GC-MS proved that the S/G ratio and the syringyl contents were directly proportional to the total lignin contents. OsCAD2 expression levels at the heading stages were consistent with their total lignin contents and their lignin histochemical assay results in the vascular bundle and cortical fiber, suggesting its important roles in rice lignin biosynthesis. However, OsMYB55/61 showed inconsistent expression patterns to total lignin contents, which may also upregulate not only lignin biosynthesis but also cellulose biosynthesis.